The impact of hippocampal impairment on task-positive and task-negative language networks in temporal lobe epilepsy. Issue 2 (February 2021) - Nenning, Karl-Heinz; Fösleitner, Olivia; Schwartz, Ernst; Schwarz, Michelle; Schmidbauer, Victor; Geisl, Gudrun; Widmann, Christian; Pirker, Susanne; Baumgartner, Christoph; Prayer, Daniela; Pataraia, Ekaterina; Bartha-Doering, Lisa; et al.
Highlights: We characterized the impact of unilateral temporal lobe epilepsy (TLE) on the functional connectome during a language task using fMRI. In left TLE, a diseased hippocampus is primarily associated with widespread impairment of task-positive language networks. In right TLE, an impaired right hippocampus led primarily to a deterioration of connectivity within the default mode network. Abstract: Objective: To study hippocampal integration within task-positive and task-negative language networks and the impact of a diseased left and right hippocampus on the language connectome in temporal lobe epilepsy (TLE). Methods: We used functional magnetic resonance imaging (fMRI) to study a homogenous group of 32 patients with TLE (17 left) and 14 healthy controls during a verb-generation task. We performed functional connectivity analysis and quantified alterations within the language connectome and evaluated disruptions of the functional dissociation along the anterior-posterior axis of the hippocampi. Results: Connectivity analysis revealed significant differences between left and right TLE compared to healthy controls. Left TLE showed widespread impairment of task-positive language networks, while right TLE showed less pronounced alterations. Particularly right TLE showed altered connectivity for cortical regions that were part of the default mode network (DMN). Left TLE showed a disturbed functional dissociation pattern along the left hippocampus to left and right inferior frontal language regions, while left and right TLE revealed an altered dissociation pattern along the right hippocampus to regions associated with the DMN. Conclusions: Our results showed an impaired hippocampal integration into active language and the default mode networks, which both may contribute to language impairment in TLE. Significance: Our results emphasize the direct role of the left hippocampus in language processing, and the potential role of the right hippocampus as a modulator between DMN and task-positive networks.